HUMAN RESOURCE MANAGEMENT – GLOBAL ECONOMY IMPORTANT FACTOR. IMPLEMENTATION OF MODERN SYSTEMS OF LABOR RESOURCE MANAGEMENT (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article examines the opinions of foreign and domestic scientists on the introduction of a modern system of human resources management. Also, the essence of the stages of evolutionary approaches to human resources management, the tasks of introducing a modern management system and ways to solve them are highlighted.